2004
DOI: 10.1172/jci20921
|View full text |Cite
|
Sign up to set email alerts
|

The renal papilla is a niche for adult kidney stem cells

Abstract: Many adult organs contain stem cells, which are pluripotent and are involved in organ maintenance and repair after injury. In situ, these cells often have a low cycling rate and locate in specialized regions (niches). To detect such cells in the kidney, we administered a pulse of the nucleotide bromodeoxyuridine (BrdU) to rat and mouse pups and, after a long (more than 2-month) chase, examined whether the kidney contained a population of low-cycling cells. We found that in the adult kidney, BrdU-retaining cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(208 citation statements)
references
References 46 publications
(44 reference statements)
8
192
1
7
Order By: Relevance
“…LRC cells was very sparse in the kidney, but they found numerous LRC cells in renal papilla [33] . In 3 dimensional culture, LRC cells in renal papilla spontaneously formed spheroids, and clones from single cell of LRC cells expressed both mesencymal and epithelial markers.…”
Section: Renal Papilla (Lrc Cd133 + )mentioning
confidence: 97%
See 1 more Smart Citation
“…LRC cells was very sparse in the kidney, but they found numerous LRC cells in renal papilla [33] . In 3 dimensional culture, LRC cells in renal papilla spontaneously formed spheroids, and clones from single cell of LRC cells expressed both mesencymal and epithelial markers.…”
Section: Renal Papilla (Lrc Cd133 + )mentioning
confidence: 97%
“…To identify the stem-like cells in kidney, Oliver et al [33,34] performed pulse label of rat and mouse pups by BrdU, and confirmed the existence of LRC cells in the kidney. LRC cells was very sparse in the kidney, but they found numerous LRC cells in renal papilla [33] .…”
Section: Renal Papilla (Lrc Cd133 + )mentioning
confidence: 99%
“…However, the location and the characteristics of renal SC are controversial. Based on the retention of bromodeoxyuridine, Oliver et al [59] identified slow cycling SC in the renal papilla of adult rat kidney suggesting the presence of an SC population capable of epithelial differentiation after ischemic injury. Based on these observations, the authors proposed that the renal papilla is a niche for the adult kidney SC in rats.…”
Section: Do Sc Contribute To Repair In Acute Tubular Injury?mentioning
confidence: 99%
“…Oliver et al [36] have isolated cells from the kidney papilla of young mice and rats that are slow-cycling cells and have characteristics of kidney stem cells. When grown in culture, these papillary cells express epithelial and mesenchymal markers, form cellular spheres, and display some evidence of plasticity with differentiation into neurons under appropriate culture conditions.…”
Section: Isolation Of Adult Kidney Stem Cellsmentioning
confidence: 99%